Caracterización eléctrica de un óxido de manganeso laminar tipo birnesita - Arias, N.P.; Becerra, M.E.; Giraldo, O. (Revista Mexicana de Física, 2015)
This paper records the characterization of a manganese oxide synthesized by solid state routes which is analogous to natural mineral called birnessite. The analysis of X-ray diffraction and average oxidation state of manganese show that the material has a lamellar structure containing manganese in oxidation states (+4) and (+3). The results of electron microscopy along with surface area and pore size measurements reveal the presence of micro and mesopores in the material. Impedance spectroscopy suggests that high frequency electrical conduction occurs in the volume and on the border of the aggregates; in contrast, ionic conductivity at low frequencies was associated with potassium ions located in the interlaminar region. AC conductivity values at low frequencies were 1.599× 10^-6 Ω^-1 cm^-1 and 6.416× 10^-5 Ω^-1 cm^-1 at high frequencies. These values are associated with an increased probability of electron jumping as frequency increases. These findings contribute to the understanding of electrical conduction processes and provides important information about its potential applications. As a result, this research will prove relevant in the field of batteries, supercapacitors and heterogeneous catalysis, among others.